Generation of targeted chlamydia trachomatis null mutants - Kari László (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE UNITED STATES OF AMERICA, 2011)
Chlamydia trachomatis is an obligate intracellular bacterial pathogen that infects hundreds of millions of individuals globally, causing blinding trachoma and sexually transmitted disease. More effective chlamydial control measures are needed, but progress toward this end has been severely hampered by the lack of a tenable chlamydial genetic system. Here, we describe a reverse-genetic approach to create isogenic C. trachomatis mutants. C. trachomatis was subjected to low-level ethyl methanesulfonate mutagenesis to generate chlamydiae that contained less then one mutation per genome. Mutagenized organisms were expanded in small subpopulations that were screened for mutations by digesting denatured and reannealed PCR amplicons of the target gene with the mismatch specific endonuclease CEL I. Subpopulations with mutations were then sequenced for the target region and plaque-cloned if the desired mutation was detected. We demonstrate the utility of this approach by isolating a tryptophan synthase gene (trpB) null mutant that was otherwise isogenic to its parental clone as shown by de novo genome sequencing. The mutant was incapable of avoiding the anti-microbial effect of IFN-γ-induced tryptophan starvation. The ability to genetically manipulate chlamydiae is a major advancement that will enhance our understanding of chlamydial pathogenesis and accelerate the development of new anti-chlamydial therapeutic control measures. Additionally, this strategy could be applied to other medically important bacterial pathogens with no or difficult genetic systems.